Cloud computing and services sciences : Third international conference, CLOSER 2015, Lisbon, Portugal, May 20-22, 2015, Revised selected papers /: Third international conference, CLOSER 2015, Lisbon, Portugal, May 20-22, 2015, Revised selected papers. (2016) - Unknown
No abstract available